2014
DOI: 10.1021/jz501373f
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Slow Photoconductivity Response of CH3NH3PbI3 Perovskites Suggesting Structural Changes under Working Conditions

Abstract: Photoconductivity measurements of CH3NH3PbI3 deposited between two dielectric-protected Au electrodes show extremely slow response. The CH3NH3PbI3, bridging a gap of ∼2000 nm, was subjected to a DC bias and cycles of 5 min illumination and varying dark duration. The approach to steady -state photocurrent lasted tens of seconds with a strong dependence on the dark duration preceding the illumination. On the basis of DFT calculations, we propose that under light + bias the methylammonium ions are freed to rotate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
321
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(357 citation statements)
references
References 45 publications
30
321
2
Order By: Relevance
“…The reverse scan increases FF, compared to the forward scan. This is consistent with the previous observation reported for any type of MAPbI 3 -based solar cells [28,31,32].…”
Section: Characterization Of a Perovskite Solar Cellsupporting
confidence: 93%
“…The reverse scan increases FF, compared to the forward scan. This is consistent with the previous observation reported for any type of MAPbI 3 -based solar cells [28,31,32].…”
Section: Characterization Of a Perovskite Solar Cellsupporting
confidence: 93%
“…Particularly intriguing is the hysteresis features in the response of the current density-voltage ( V J − ) curves [10][11][12][13] that have been related to a number of different explanations, as ferroelectric properties of the perovskite materials, [14][15][16] delayed electronic trapping processes, [17] or slow ion migration. [11,18,19] The recognition that the solar cell performance is heavily affected by time scale of the measurement and preconditioning procedures [9,17,20,21] has raised many concerns about the stability of the device and reliability for long time operation.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported on this effect and speculated about the causes. [18][19][20][21][22] Some recent articles present cell designs that minimize this hysteresis. 23,24 In this article, we describe the hysteresis effect in additional detail.…”
Section: Introductionmentioning
confidence: 99%
“…18 All three of these possibilities remain in the debate. 5,19,20,20,25 Along with the addition of crystal size effects 21 . It has been proposed that an optimum mesoporous TiO 2 film thickness minimizes the JV hysteresis.…”
Section: Introductionmentioning
confidence: 99%